2012
DOI: 10.1007/s10815-012-9848-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitrification on mitochondrial membrane potential in human metaphase II oocytes

Abstract: Objective The aim of this study was to evaluate the impact of vitrification on mitochondrial membrane potential (ΔΨm) in human metaphase II (MII) oocytes, and the changes of ΔΨm on thawed MII oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…In the present study, a significant decrease in fluorescence intensity of oocytes subjected to vitrification was observed (Figure ). Our findings are consistent with results of studies on the oocytes of other species (Chen et al., ; Lei et al., ; Nazmara et al., ; Zander‐Fox et al., ). Zander‐Fox et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, a significant decrease in fluorescence intensity of oocytes subjected to vitrification was observed (Figure ). Our findings are consistent with results of studies on the oocytes of other species (Chen et al., ; Lei et al., ; Nazmara et al., ; Zander‐Fox et al., ). Zander‐Fox et al.…”
Section: Discussionsupporting
confidence: 93%
“…() suggested that the decrease in mitochondrial activity may be due to osmotic stress within the oocyte caused by exposure to high level of cryoprotectants which are used in vitrification procedure to prevent ice crystal formation. Other authors suggested that non‐physiological temperatures, phase transition, pH instability and osmotic pressure change during dehydration–rehydration might also be factors affecting the function or number of mitochondria (Chen et al., ; Lei et al., ; Nazmara et al., ; Shi et al., ). Taking together, we hypothesize that the fluorescence intensity of MitoTracker ® Red CMXRos affected by vitrification may reflect a decreasing meiotic and developmental competence of oocyte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei et al [17,18] suggested that vitrification significantly affects mitochondrial function and caused the failure of embryo development after fertilization in both mouse oocytes and human IVM oocytes. Jones et al [15] and Chen et al [5] used programmed freezing method and vitrification method, respectively, to cryopreserve human MII-stage oocytes; both groups reported that the irreversible loss of high DWm in thawed oocytes may be associated with their poor developmental ability after in vitro fertilization. Zander-Fox et al [50] showed that mouse oocytes vitrification altered mitochondrial distribution and membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…The information available on the neonatal outcome and the long-term follow-up of children conceived after oocyte cryopreservation is limited (Chian et al, 2008(Chian et al, , 2014Noyes et al, 2009;Wennerholm et al, 2009;Cobo et al, 2014) and only small studies have specifically addressed the safety of oocyte vitrification (Coticchio et al, 2009;Bonetti et al, 2011;Chen et al, 2012;Forman et al, 2012;Khalili et al, 2012;Monzo et al, 2012;Dominguez et al, 2013;Gugliemo et al, 2014;Konc et al, 2014;Nohales Có rcoles et al, 2014;Palmerini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%